Solving a recurrence relation using iteration method
Consider this example :
T(n) = T(7n/8) + 2n
I assumed T(1) = 0
and tried to solve it in the following way
T(n) =开发者_开发技巧 T(7n/8) + 2n
= T(49n/64) + 2.(7n/8) + 2n
= T(343n/512) + 2.(7n/8).(7n/8)+ 2.(7n/8) + 2n
= T(1) + 2n ( (7n/8)^i + ..... + 1)
but I could not come to any conclusion about this. I am confused about what should I do in the next step.
Your approach is sound, but you'll see what to do if you rewrite it slightly differently:
T(n) = T((7/8)^1 * n) + 2 * (7/8)^0 * n
= T((7/8)^2 * n) + 2 * (7/8)^1 * n + 2 * (7/8)^0 * n
= T((7/8)^3 * n) + 2 * (7/8)^2 * n + 2 * (7/8)^1 * n + 2 * (7/8)^0 * n
.
.
.
= T((7/8)^k * n) + 2 * n * sum j = 0 to k-1 (7/8)^j
Now, let k
tend to infinity and see what happens. It would help if you're familiar with geometric series.
T(n) = T(7n/8) + 2n = 2n * (1 + 7/8 + (7/8)^2 + ... (7/8)^Z) + T(1) where Z = ?
The only trick is finding Z. I bet a log will help. Sorry it is late, and I am not thinking straight, but ... you should not need to add multiple 2n.
Edit: Z is how many time you need to multiply n by 7/8 until you get 1.
So, n * 7^Z / 8^Z = 1
(7/8)^Z = 1/n
(8/7)^Z = n
You want to solve for Z.
What you got there in the last line is a geometric series and there is a formula to simplify such a sum.
精彩评论